PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. PERJAMUAN RASA RAJA JAKARTA SELATAN - Dea Ayu Bagus Oka (Al Hasanah Barokah Foundation, 2024)
The purpose of this research is to find out whether the work environment and work discipline influence employee performance at PT. Taste of the King's Banquet, South Jakarta. The method used is quantitative. The sampling technique used saturated sampling and a sample of 75 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. There is a positive and significant influence of the work environment on employee performance at PT. King's Taste Banquet This can be proven from the simple linear regression equation Y=29.090+0.397 0.261X2, meaning the value (a) or constant is 31.492. Simultaneously there is a positive and significant influence between the work environment and work discipline on employee performance. This can be proven from the multiple linear regression equation Y=26.367+0.310X1+0.144X2. The regression value is 0.310 Regression value 0.144X2 (positive)